FAITH, INTOLERANCE, VIOLENCE AND BIGOTRY: Legal and Constitutional Issues of Freedom of Religion in Indonesia (JOURNAL OF INDONESIAN ISLAM, 2016)
Religious intolerance and bigotry indeed is a contributing factor in social and political conflict including manifestations of terrorist violence. While freedom of religion is enshrined in Indonesia’s Constitution, social practices and governmental regulations fall short of constitutional and international law guarantees, allowing institutionalised bias in the treatment of religious minorities. Such bias inhibits Indonesia’s transition to a fully-functioning pluralistic democracy and sacrifices democratic ideals of personal liberty and freedom of expression for the stated goals of religious and social harmony. The Ahok case precisely confirms that. The paper examines the constitutional bases of freedom of religion, Indonesia’s Blasphemy Law and takes account of the history and tenets of Pancasila which dictate a belief in God as the first principle of state ideology. The paper argues that the Indonesian state’s failure to recognise the legitimacy of alternate theological positions is a major obstacle to Indonesia recognising the ultimate ideal, enshrined in the national motto, of unity in diversity.